Balancing Global and Local Standards: A Study of Al-'Arabiyyah Baina Yadaik in the Context of Indonesian Islamic Education - Zakiyah, Zakiyah; Nasaruddin, Nasaruddin; Taufik, Mirwan Akhmad; Huda, Hisbullah; Baihaqi, M.; Rady, Mohammed Jassim Mohammed (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study evaluates the suitability of the textbook Al-‘Arabiyah Baina Yadaik based on Amani and Awatif’s criteria and the Directorate General of Islamic Education Decree (KEPDIRJENPENDIS) No. 3302 of 2024. It examines: (1) the textbook’s quality per Amani and Awatif’s standards, (2) its alignment with KEPDIRJENPENDIS policy, and (3) its strengths and weaknesses. Using qualitative library research and content analysis, data were collected through documentation and analyzed descriptively. The results show that the textbook meets Amani and Awatif’s standards, though it lacks a reference list and does not adequately address individual learner differences. According to KEPDIRJENPENDIS, it is suitable for grades 7–9 students. Strengths include QR-code features for interactive learning, the four Arabic language skills development, and integration of Arab-Islamic cultural values. In conclusion, Al-‘Arabiyah Baina Yadaik is useful for Arabic language education and aligns with current educational standards and policies.